Pregnancy-associated breast cancer - diagnosis, treatment and outcomes for women and their offspring - Martyna Maria Zielińska; Natalia Zarankiewicz; Aleksandra Kuchnicka; Katarzyna Kosz; Bogumiła Ciseł (Kazimierz Wielki University, 2020)
Introduction: Pregnancy-associated breast cancer (PABC) is the most common malignancy in pregnant women with an incidence of 1 in 3-10 thousand pregnancies. It is mostly defined as breast cancer diagnosed during pregnancy or within 1 year postpartum. The number of PABCs is going to raise due to the trend of delaying childbearing.  Purpose: This review summarizes data on the occurrence and characteristics of PABC. The analysis comprises diagnosis and proper treatment of BC during pregnancy. Prognosis of women and their offspring are emphasized.  Material and methods: The review is based on publications mainly from 2010 to 2019 and 5 articles from 1994-2008 collected on the PubMed.   Results: The sensitivity of breast ultrasonography (USG) in pregnancy is 70-100% and it is considered as safe for the fetus. Staging evaluation in pregnant women consists of chest x-ray, liver USG and non-contrast bone MRI. 71-88% of PABCs are invasive ductal carcinomas. Treatment consists of breast surgery regardless of time and optionally, chemotherapy from the 2nd trimester. Radiotherapy, tamoxifen and trastuzumab are contraindicated in PABC. Therapeutic abortion does not improve oncological outcome. Overall prognosis is similar for both pregnant and non-pregnant patients with similar type and stage of BC. The rate of congenital malformations is 1,3% for both children of PABC patients treated with chemotherapy and born from women without chemotherapeutic treatment. The most frequent obstetrical complication of PABC treatment is preterm delivery.  Conclusions: Pregnancy does not impact oncologic outcome, if the treatment is appropriate. PABC patients have survival rates consistent with the stage of disease. Proper treatment of PABC does not increase the risk of congenital malformations and is relatively safe for the fetus.